Bacterial microbiome in tropical lichens and the effect of the isolation method on culturable lichen-derived actinobacteria - Trinset Weeraphan; Achiraya Somphong; Vasun Poengsungnoen; Kawinnat Buaruang; Enjuro Harunari; Yasuhiro Igarashi; Somboon Tanasupawat; Wongsakorn Phongsopitanun (Scientific Reports, 2023)
Abstract Ten samples of tropical lichens collected from Doi Inthanon, Thailand, were explored for the diversity of their bacterial microbiomes through 16S rRNA-based metagenomics analysis. The five predominant lichen-associated bacteria belonged to the phyla Proteobacteria (31.84%), Planctomycetota (17.08%), Actinobacteriota (15.37%), Verrucomicrobiota (12.17%), and Acidobacteriota (7.87%). The diversity analysis metric showed that Heterodermia contained the highest bacterial species richness. Within the lichens, Ramalina conduplicans and Cladonia rappii showed a distinct bacterial community from the other lichen species. The community of lichen-associated actinobacteria was investigated as a potential source of synthesized biologically active compounds. From the total Operational Taxonomic Units (OTUs) found across the ten different lichen samples, 13.21% were identified as actinobacteria, including the rare actinobacterial genera that are not commonly found, such as Pseudonocardia, Kineosporia, Dactylosporangium, Amycolatopsis, Actinoplanes, and Streptosporangium. Evaluation of the pretreatment method (heat, air-drying, phenol, and flooding) and isolation media used for the culture-dependent actinobacterial isolation revealed that the different pretreatments combined with different isolation media were effective in obtaining several species of actinobacteria. However, metagenomics analyses revealed that there were still several strains, including rare actinobacterial species, that were not isolated. This research strongly suggests that lichens appear to be a promising source for obtaining actinobacteria.